Contrast-to-noise ratios of different dental restorative materials: An in-vitro cone beam computed tomography study - Seval Bayrak; Emine Şebnem Kurşun Çakmak; Hakan Kamalak (European Oral Research)
Purpose In radiological views, strong beam hardening and streaking artifacts occur due to high-density structures and polyenergetic X-ray beams, and these lead to misdiagnosis. This study was performed in vitro to compare the contrast-to-noise ratio (CNR) of commonly used dental restorative materials by using Cone Beam Computed Tomography (CBCT) images with and without artifact reduction (AR) mode. Materials and Methods A total of 108 molar teeth were restored with nine different groups of restorative materials, with each group containing 12 teeth. Teeth were placed in a dry human mandible and scanned, one by one, via Planmeca 3D ProMax (Planmeca, Helsinki, Finland) with and without AR mode. Images were analyzed using ImageJ software (National Institutes of Health, Bethesda, MD) to calculate the CNR. Results CNR was calculated to be the highest in compomer (Glassiosite) images without AR mode (mean: 3.36) and with AR mode (mean: 3.61). CNR was calculated to be the lowest in amalgam (Tytin) images without AR mode (mean: 0.21) and with AR mode (mean: 0.23). A significant difference was found between materials in terms of CNR measurements (p ≤ 0.05). CNR measurements were increased after the AR mode application (p ≤ 0.05). Conclusion AR mode was effective in reducing artifacts arising from dental materials on CBCT images, so it is necessary to use AR mode for correct diagnoses.